Managing the change of organizational culture in cross-border mergers and acquisitions: The role of post-acquisition integration in organizational culture change - Hirvonen, Eve (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Over the years, cross-border mergers and acquisitions have become a popular strategic option for variety of firms. Companies often seek rapid growth through acquiring potentially valuable enterprises or attempting to enhance their organization’s profitability by merging with other firms. However, managing the change of organizational culture is a major managerial challenge as companies often confront difficulties when merging two previously autonomous organizational cultures into one, joint organizational culture. Therefore, the purpose of this study is to increase understanding related to the challenges and possibilities concerning the management of organizational culture change in cross-border mergers and acquisitions. The research question “How to manage the change of organizational culture in cross-border mergers and acquisitions?” is analysed in relation to the theories presented in this thesis regarding organizational culture, organizational change and acculturation as well as in relation with the collected empirical data. The research question is divided into three sub-questions according to the following: (1) “What is the role of organizational culture in organizations?”, (2) “How to manage organizational change in mergers and acquisitions?” and (3) “How to manage organizational culture change through acculturation?”. The thesis is conducted as a qualitative case study research including three personal interviews and one group interview. The interviews were conducted as a combination of semi-structured and unstructured interviews. Theories related to organizational culture, the management of change as well as acculturation are studied and further analysed in relation to empirical material collected by the researcher. Research findings indicate that that several factors can influence the success of managing the organizational culture change in cross-border mergers and acquisitions. Factors such as defining the preferred acculturation model prior the merger; managing the resistance of change; open communication; acknowledgement of local culture and cultural differences; involvement of personnel in change processes; as well as the formulation and implementation of comprehensive change plans proved to be important factors with relation to successful management of organizational culture change